Challenges and opportunities for characterizing cognitive aging across species - Roberson, Erik D.; DeFazio, R. A.; Barnes, Carol A.; Alexander, Gene E.; Bizon, Jennifer L.; Bowers, Dawn; Foster, Thomas C.; Glisky, Elizabeth L.; Levin, Bonnie E.; Ryan, Lee; Wright, Clinton B.; Geldmacher, David S. (Frontiers in Aging Neuroscience, 2012)
The gradual decline of cognitive ability with age, even in the absence of overt brain disease, is a growing problem. Although cognitive aging is a common and feared accompaniment of the aging process, its underlying mechanisms are not well understood and there are no highly effective means to prevent it. Additional research on cognitive aging is sorely needed, and methods that enable ready translation between human subjects and animal models stand to provide the most benefit. Here and in the six companion pieces in this special issue, we discuss a variety of challenges and opportunities for studying cognitive aging across species. We identify tests of associative memory, recognition memory, spatial and contextual memory, and working memory and executive function as cognitive domains that are age-sensitive and amenable to testing with parallel means in both humans and animal models. We summarize some of the important challenges in using animal models to test cognition. We describe unique opportunities to study cognitive aging in human subjects, such as those provided by recent large-scale initiatives to characterize cognition in large groups of subjects across the lifespan. Finally, we highlight some of the challenges of studying cognitive aging in human subjects.